Commodification of education in the era of globalization - Abdul Razak, Mohd. Abbas (SHAS Mosque, IIUM, 2017)
In the past centuries, education was regarded as a medium of creating a good individual and citizen. The philosophy of education is designed to guide in producing the type of individuals the state wants to create. The analogy of the educator is like that of a blacksmith who moulds the iron into his desired shape while it is still red-hot. Likewise, the learner can be moulded into character by the parents, teachers and school system during his or her tender age. Compared to the present, in the olden days, all forms of education, regardless formal, informal and non-formal are all directed towards transference of knowledge, values, skills, culture, language, religious teachings, etc. from the old to the new and upcoming generation. Education during the bygone centuries had a more holistic and comprehensive concept in bringing up an integrated personality. Modern day education with its technology mediated learning has deprived the learner from many of the real life experience. The learner has been confined to the four walls of the classroom. Ancient philosophers have always emphasised the fact that any good and ethical activities under the sun can be a learning experience and enrichment to the learner. Many experts in education too have highlighted that if an individual learns to remember he or she will forget and at the same time if the individual learns to understand, he or she will remember.